1995
DOI: 10.1016/0034-6667(94)00142-7
|View full text |Cite
|
Sign up to set email alerts
|

Jurassic palynology from a borehole in the Champagne area, France-correlation of the lower Callovian-middle Oxfordian using sequence stratigraphy

Abstract: The cored borehole A901, drilled by the National Agency for the Management of Radioactive Waste at Montcornet, in Champagne, on the northeastern border of the Paris Basin, provided a continuous section from the Hettangian to the lower Kimmeridgian. Samples taken at regular intervals yielded marker dinoflagellate cysts of the northwest European domain that have been correlated with ammonite zones.The earliest dinoflagellate species appear in the upper Sinemurian (976 m, Obtusum zone), whereas the lowest interse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
5

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 21 publications
1
6
0
5
Order By: Relevance
“…Detrital organic matter in claystone samples do not exceed $1.4 wt.% (Disnar et al, 1996;Cassagnabère, 2001;Claret et al, 2004;Gaucher et al, 2004). Chemical studies showed that terrestrial organic matter is ubiquitous in the clay formation, whereas marine-derived organic matter is mostly observed at the Callovian-Oxfordian transition corresponding to the MCZ (Fauconnier, 1995;Disnar et al, 1996;Michels, 2001;Hautevelle et al, 2007).…”
Section: Petrography -Previous Workmentioning
confidence: 93%
“…Detrital organic matter in claystone samples do not exceed $1.4 wt.% (Disnar et al, 1996;Cassagnabère, 2001;Claret et al, 2004;Gaucher et al, 2004). Chemical studies showed that terrestrial organic matter is ubiquitous in the clay formation, whereas marine-derived organic matter is mostly observed at the Callovian-Oxfordian transition corresponding to the MCZ (Fauconnier, 1995;Disnar et al, 1996;Michels, 2001;Hautevelle et al, 2007).…”
Section: Petrography -Previous Workmentioning
confidence: 93%
“…-for references see e.g., ŠEJNOHOVÁ et al, 2003). Semiquantitative estimates of algal populations were deduced from slides, and individual species were classified into three categories: (1) up to 1% of individuals revealed, (2) up to 50% of individuals, and (3) more than 50% of individuals of a particular assemblage (KINROSS et al, 1993;FAUCONNIER, 1995;GAISER and JOHANSEN, 2000;HUSA et al, 2004;KOMÁREK and SUKAČOVÁ, 2004). Approximately 500 cells per sample were observed.…”
Section: Methodsmentioning
confidence: 99%
“…France, Fauconnier, 1995, Barski 1999, 2012, Huault, 1999, Williams & Bujak 1985 La plupart des études concernant le domaine sub-boréal sont corrélées avec les zones d'Ammonites. En Angleterre les biozones des kystes des dinoflagellés, couvrent tout le jurassique, et, ont été bien corrélées avec les zones standard d'ammonites (Cope et al, 1980a, 1980b, In: Woollam et Riding, 1983Riding et Thomas, 1992 (Woollam et Riding, 1983).…”
Section: 2domaine Sub-boréal (Europe Du Nord-ouest )unclassified
“…Ctenidodinium sellwoodii caractérise dans l'ensemble des bassins de l'Europe du Nord-Ouest, une biozone à Cse correspondante au Bathonien moyen-Callovien inférieur (Riding et Thomas, 1992). Sarjeant (1979) (Huault,1999) ou la région de Champagne (Fauconnier, 1995) (Fauconnier, 1995, Huault,1999.…”
Section: 2domaine Sub-boréal (Europe Du Nord-ouest )unclassified
See 1 more Smart Citation